Prescribed Norms : Women and Health in Canada and the United States since 1800 - Warsh, Cheryl Krasnick, 1957- (Book collections on Project MUSE., 2010)
"By comparing ritual practices of various cultures, Prescribed Norms demonstrates how looking at women's health through a masculine lens has distorted current medical understandings of menstruation, menopause, and childbirth, and has often led to faulty medical conclusions. Warsh also illuminates how the shift from informal to more formal, institutionalized treatment impacts both women's health care and women's roles as health practitioners"--Pub. info